116 An Experimental Study to Assess the Professional and Social Consequences of Tardive Dyskinesia. (April 2020) - Ayyagari, Rajeev; Goldschmidt, Debbie; Mu, Fan; Caroff, Stanley N.; Carroll, Benjamin
Abstract: Study Objective: Evaluate the impact of orofacial tardive dyskinesia (TD) symptoms on the professional and social lives of patients with TD. Background: TD, a movement disorder affecting the face and extremities, may arise in patients taking antipsychotics. The impact of social stigma on the professional and social lives of patients with orofacial manifestations of TD has not been thoroughly examined. Methods: This study is an experimental, randomized digital survey of a general population sample. Three component surveys were developed, corresponding to employment, dating, and friendship domains. For each domain, participants were randomized 1:1 into either a test group (who viewed a video of a scripted interview with a standardized patient actor depicting TD movements) or a control group (who viewed the same actors but without TD movements), and asked about their impressions of the video subject. Actor simulations were validated by physicians familiar with TD and rehearsed to simulate a total Abnormal Involuntary Movement Scale score between 6 and 10. Statistical comparison was made using Wilcoxon sign-rank or chi-squared tests for continuous and categorical variables, respectively. Results: A total of 800 respondents completed each survey. In all domains, respondents had more-negative perceptions of actors portraying TD movements than of the same actors without movements. Regarding employment, 34.8% fewer respondents in the test group versus the control group agreed that the actor would be suitable for client-facing jobs (P<0.001). Regarding dating, the proportions of respondents who agreed that they would like to continue talking to the actor and who would be interested in meeting them for coffee/drink were 25.0% and 27.2% lower, respectively, in the test group than in the control group (P<0.001). Regarding friendship, the proportions of respondents who rated the actor as interesting and who would be interested in friendship with them were 18.8% and 16.5% lower, respectively, in the test group than in the control group (P<0.001). Conclusions: Actors simulating orofacial TD movements were perceived to be statistically significantly less likely to move forward in a job interview, be considered as a potential romantic partner, or be a new friend. This is the first study to quantify the stigma faced by people with TD in a variety of professional and social situations. Funding Acknowledgements: This study was funded by Teva Pharmaceuticals, Petach Tikva, Israel.